Efficient carbon-supported heterogeneous molybdenum-dioxo catalyst for chemoselective reductive carbonyl coupling. Issue 11 (15th May 2017) - Liu, Shengsi; Li, Jiaqi; Jurca, Titel; Stair, Peter C.; Lohr, Tracy L.; Marks, Tobin J.
Abstract : Selective carbonyl coupling, high symmetric ether selectivity. Abstract : Reductive coupling of various carbonyl compounds to the corresponding symmetric ethers with dimethylphenylsilane is reported using a carbon-supported dioxo-molybdenum catalyst. The catalyst is air- and moisture-stable and can be easily separated from the reaction mixture for recycling. In addition, the catalyst is chemoselective, thus enabling the synthesis of functionalized ethers without requiring sacrificial ligands or protecting groups.